Literature Review: Efektivitas dan Efek Samping PCSK9 Inhibitor (Proprotein Convertase Subtilisin/Kexin Type 9 Inhibitor) dengan Golongan Statin pada Pasien Penderita Kolesterol - Adhwa'a Kaylla Affandhy; Hadi Sudarjat; Indah Laily Hilmi; Jahra Almas Shadrina; Fadya Laila Dzannuba Laila Dzannuba (Poltekkes Kemenkes Padang, 2025)
Cholesterol is an essential molecule in the human body, but excessive levels can lead to various diseases, including hypercholesterolemia. The management of high cholesterol involves the use of statins and PCSK9 inhibitors. This study aims to compare the effectiveness and side effects of these two drug classes.This study is a literature review conducted from August to September using articles from the PubMed database with keywords related to PCSK9 inhibitors and statins. The data were analyzed through bibliometric analysis using VOSviewer software with keywords such as PCSK9 inhibitor, alirocumab, bococizumab, and evolocumab.The results showed that PCSK9 inhibitors could reduce LDL-C levels by 57-61% with a good safety profile, although side effects such as injection site reactions were observed. In comparison, statins reduced LDL-C levels by 18-55% and increased HDL-C levels by up to 15%, but their side effects included muscle disorders and liver function impairment. PCSK9 inhibitors provide an additional solution for patients who do not respond optimally to statins. Conclusion: PCSK9 inhibitors are effective in lowering LDL-C in patients who have difficulty achieving target levels with statin therapy alone.